2017
DOI: 10.1002/cnma.201700010
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Multifunctional Bionanocomposite Foams with a Chitosan Matrix Reinforced by Nanofibrillated Cellulose (ChemNanoMat 2/2017)

Abstract: Multifunctional bionanocomposite foams with a 3D interconnected network were made from a chitosan matrix reinforced with nanofibrillated cellulose. The bionanocomposite foams display a number of interesting properties, including the fact that they are very soft but have high durability, high thermal insulation, underwater oleophobicity, and high biocompatibility for boosting the growth of L929 cells. These results indicate that the bionanocomposite foams have great potential in a wide range of applications, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As shown in Figure 4c, Figure 4d, Figure 4e and Figure 4f; MCC aggregate bundles bonded to chitosan sheets randomly. Previous studies also showed similar structures; Wang et al (2017) investigated the microstructure of chitosan-nanofibrillated cellulose (NFC) foams and showed that the NFC bonded to the cell walls/sheets randomly.…”
Section: Morphologymentioning
confidence: 87%
See 4 more Smart Citations
“…As shown in Figure 4c, Figure 4d, Figure 4e and Figure 4f; MCC aggregate bundles bonded to chitosan sheets randomly. Previous studies also showed similar structures; Wang et al (2017) investigated the microstructure of chitosan-nanofibrillated cellulose (NFC) foams and showed that the NFC bonded to the cell walls/sheets randomly.…”
Section: Morphologymentioning
confidence: 87%
“…The T %50 found between 341,3 °C and 365 °C. Wang et al (2017) found the T %50 between 300 °C and 350 °C for chitosan-CNF foams. Yildirim et al (2014) found the results between 300 °C and 335 °C for CNF-starch foams.…”
Section: Thermogravimetric Analysismentioning
confidence: 94%
See 3 more Smart Citations